2018
DOI: 10.1098/rsos.180205
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dimming light-emitting diode street lights on light-opportunistic and light-averse bats in suburban habitats

Abstract: Emerging lighting technologies provide opportunities for reducing carbon footprints, and for biodiversity conservation. In addition to installing light-emitting diode street lights, many local authorities are also dimming street lights. This might benefit light-averse bat species by creating dark refuges for these bats to forage and commute in human-dominated habitats. We conducted a field experiment to determine how light intensity affects the activity of the light-opportunistic Pipistrellus pipistrellus and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 55 publications
0
16
0
Order By: Relevance
“…As evidence for the detrimental impacts of artificial light at night continues to grow, attention is now turning towards how best to mitigate its ecological effects. New lighting technologies allow for greater flexibility in the control of light emissions from individual street lights, and so options such as dimming, part‐night lighting and altering the spectrum of lights are being explored (Azam et al, ; Day, Baker, Schofield, Matthews, & Gaston, ; Gaston, Davies, Bennie, & Hopkins, ; Rowse, Harris, & Jones, ; Spoelstra et al, ). While dimming and part‐night lighting are useful in reducing light pollution overall, the opportunity to deliver benefits for bats may be limited.…”
Section: Introductionmentioning
confidence: 99%
“…As evidence for the detrimental impacts of artificial light at night continues to grow, attention is now turning towards how best to mitigate its ecological effects. New lighting technologies allow for greater flexibility in the control of light emissions from individual street lights, and so options such as dimming, part‐night lighting and altering the spectrum of lights are being explored (Azam et al, ; Day, Baker, Schofield, Matthews, & Gaston, ; Gaston, Davies, Bennie, & Hopkins, ; Rowse, Harris, & Jones, ; Spoelstra et al, ). While dimming and part‐night lighting are useful in reducing light pollution overall, the opportunity to deliver benefits for bats may be limited.…”
Section: Introductionmentioning
confidence: 99%
“…Bats also respond differently to differences in light intensity: Myotis spp. are more active in areas of lower light intensity, but Pipistrellus pipistrellus activity increases with intensity (Rowse et al 2018). Individual fitness may be reduced in light-shy species such as Nyctalys leislerii, Myotis spp., and Plecotus spp., due to their avoidance of lit areas to prevent exposure to predators, or because insects are attracted away from dark foraging patches (Fure 2012).…”
Section: Roadsmentioning
confidence: 99%
“…were more active under white, green, or orange LED lights (Spoelstra et al 2017, Zeale et al 2018. Low-intensity lighting is likely to reduce light spill, mediating the impact on light-averse species (Rowse et al 2018). The varied responses of bats to the presence of different artificial light types, spectra and intensities suggest that a single mitigation method for ALAN is unlikely to benefit all bat species.…”
Section: Legislation and Mitigation Measuresmentioning
confidence: 99%
“…Only a few studies on bats and ALAN conducted in Europe have incorporated aerial insect samples to examine the predator-prey relationship [ 26 , 38 , 39 ]. These studies found that ALAN altered insect communities and that more insects were captured when ALAN was introduced.…”
Section: Introductionmentioning
confidence: 99%